Identification of a Novel Heterozygous Mutation in the EIF2B4 Gene Associated With Vanishing White Matter Disease - Tian, Yun; Liu, Qiong; Zhou, Yafang; Chen, Xiao-Yu; Pan, Yongcheng; Xu, Hongwei; Yang, Zhuanyi (Frontiers in Bioengineering and Biotechnology, 2022)
Vanishing white matter disease (VWM) is one of the most common childhood inherited leukoencephalopathy with autosomal recessive inheritance. Mutations in the 5 genes EIF2B1-5 had been identified as the major cause of VWM. In this study, targeted gene capture sequencing panel composed of 160 known pathogenic genes associated with leukoencephalopathies was performed in a large family affected with adult-onset VWM, and a novel heterozygous missense mutation (c.1337G>A: [p. R446H]) in EIF2B4 (NM_001034116.2) was detected. Further functional study in HEK293 cells showed dramatically reduced EIF2B4 protein level in the mutated group compared with the wild-type group. This study revealed a heterozygous missense mutation (c.1337G>A: [p. R446H]) in EIF2B4, which was potentially associated with adult-onset mild phenotype of VWM. Different from previously reported, autosomal dominant inheritance could also be observed in adult-onset VWM.